Analysis Of The Effect Of Current Ratio And Net Profit Margin On Stock Prices In Food And Beverage Companies Listed On The Indonesia Stock Exchange - Asazatulo Giawa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2023)
This study aims to test the Effect of Current Ratio and Net profit Margin on Stock Prices listed on the Indonesia Stock Exchange 2018-2020. In this study there are 2 independent variables, namely Current Ratio and Net Profit Margin and 1 dependent variable, namely Stock Price. The sampling method carried out in this study is the purposive sampling method. The population in this study was 26 companies and then that met purposive sampling of 10 companies. The type of regression model used in this study was multiple regression, then to test the research in multiple regression using Statistical Product and Service Solution (SPSS) version 22.